The Influence of Family Support and Maternal Preparedness on Anxiety in Pregnant Women Before Delivery at Bongo Nol Health Center - Febrina Idas Wara; Sulistiyah Sulistiyah; Reny Retnaningsih (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Anxiety in pregnant women is often characterized by intense fear or panic, and if left unaddressed, it can lead to various complications such as prolonged labor, maternal fatigue, and even labor stall. This study aimed to determine the relationship between family support and maternal preparedness with the anxiety levels of pregnant women prior to childbirth. The research utilized a quantitative design with a cross-sectional approach, conducted in the working area of the Bongo Nol Health Center. The study population consisted of pregnant women in their second and third trimesters (TM II and TM III). A total of 40 pregnant women participated in the study, selected through simple random sampling. Data were collected using questionnaires designed to assess family support, maternal preparedness, and anxiety levels. The results revealed that 20% of the pregnant women who received inadequate family support experienced severe anxiety, with a statistically significant p-value of 0.001. Similarly, 15% of mothers with lower levels of preparedness reported severe anxiety, also with a p-value of 0.001. These findings suggest a significant relationship between both family support and maternal preparedness with anxiety levels in pregnant women prior to delivery. The study concludes that increased family support and maternal readiness can help reduce anxiety levels in pregnant women, particularly in the lead-up to childbirth. Healthcare providers should prioritize interventions to strengthen family involvement and support maternal readiness, especially for women at risk of high anxiety, to improve birth outcomes and maternal well-being. Future research should explore additional factors contributing to anxiety and the effectiveness of targeted interventions for high-risk pregnancies